Modelling of rotor defects in squirrel cage induction motors using the time stepping numerical field analysis - Tami, Abdelkader (1995)
The arrival of cheap and fast microcomputers has stimulated the development of machine condition monitoring systems. Such systems measure one or more machine performance parameters, with a view to detecting the early signs of failure and initiating some form of action. To help developing these systems, a thorough knowledge of the behaviour of the machine in its post-fault condition must be well known and well understood. With this view in mind, a simple, yet reasonably accurate method of analysing the induction machine magnetic circuit under normal and abnormal conditions at moderate cost has been developed.